Beyond toilets and targets: sanitation mission in India. Issue 3 (3rd April 2017) - Kumar, Avanish
ABSTRACT: In an attempt to address Sustainable Development Goal 6, the Government of India's initiative, Swachh Bharat Mission (SBM), aims to make India open-defecation free by 2018. This viewpoint analyses the consequences of SBM from the perspective of women and water in the context of toilets. With the construction of toilets for 2.4 million people, the vulnerability of women is expected to worsen as available water is scarce. The viewpoint concludes that construction of toilets as a target is difficult to achieve and sustain without green technology design that overcomes the constraints of water and women.